Hungarian Monitoring, 15 March 1989 . [Magyar rádiófigyelő], 1989. március 15 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - "Genius of the Carpathians", mocking title given to Ceauşescu by the New York Times - International press coverage of the Hungarian March 15 celebrations - Gorbachev talks about agricultural reform at the CPSU Central Committee plenum Domestic Affairs: - Várkonyi-Thatcher meeting in London - Survey of reports on March 15 celebrations in Budapest and the countryside - At commemoration in front of Academy, Gáspár Miklós Tamás remembers Chain Bridge beatings one year ago - Interior Ministry police lieutenant-colonel on preparations for March celebrations - Hungarian-American Friendship Society can operate legally after Békéscsaba court approval - Peaceful March 15 celebrations end with alternative groups' candlelit procession Külpolitika: - "A Kárpátok géniusza" - Ezt a gúnyos titulust Ceauşescu kapta a New York Times-tól - Külföldi sajtójelentések a magyar márciusi ünnepségekről - Gorbacsov az SZKP KB plénumán a mezőgazdasági reformról beszélt Belpolitika: - Várkonyi - Thatcher találkozó Londonban - Körkapcsolásos beszámolók a budapesti és vidéki március 15-ei ünnepségekről - Tamás Gáspár Miklós az egy év előtti Lánchídi verésre emlékezik az Akadémia előtti megemlékezésében - A márciusi ünnepségsorozat előkészületeiről a Belügyminisztérium rendőr-alezredese - Békéscsabán - Bírósági jóváhagyás után - Legálisan működhet a Magyar-Amerikai Baráti Társaság - A békés március 15-i ünnepségek az alternatív szervezetek fáklyás felvonulásával ért véget